Pengaruh Biaya Produksi, Biaya Penilaian, dan Biaya Kegagalan Terhadap Net Profit Margin (NPM) Pada Pelaku UMKM Sektor Fashion Streetwear di Kota Bandung Periode 2022-2024 - Sukmariza Abelianti; Santi Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
costs on Net Profit Margin (NPM) among micro, small, and medium enterprises (MSMEs) in the fashion streetwear sector in Bandung City. The research adopts a quantitative approach using a verificative method. The data used in this study are primary data collected through the distribution of questionnaires to the owners or managers of 10 fashion streetwear brands in Bandung City during the observation period from 2022 to 2024, resulting in a total of 30 observations. The data were analyzed using multiple linear regression with the assistance of IBM SPSS version 25. The research findings indicate that individually, production costs do not have a significant effect on Net Profit Margin, while appraisal costs and failure costs have a positive and significant effect on Net Profit Margin. Simultaneously, production costs, appraisal costs, and failure costs have a significant effect on Net Profit Margin, with a coefficient of determination of 0.965. This result indicates that 96.5% of the variation in Net Profit Margin can be explained by the three independent variables, while the remaining variation is influenced by other factors outside the research model. This study concludes that quality cost management, particularly appraisal costs and failure costs, plays a crucial role in improving the profitability of MSMEs in the fashion streetwear sector. The findings are expected to serve as considerations and a basis for decision-making for MSME owners in managing costs more efficiently to enhance financial performance and business competitiveness.